Antipenetration Performance of Honeycomb Shelter under Two Repeat Projectile Strikes - Qifan Wang; Liusheng Chu; Jie Li; Jianhu Sun; Sheng Luo; Lei Mao (Shock and Vibration)
Antipenetration performance of honeycomb shelter under two repeat projectile strikes is investigated via test and numerical simulation. Among them, there are two kinds of test targets: cylindrical honeycomb structure target and reinforced concrete target; a numerical simulation target is a honeycomb-structure target composed of hexagonal honeycomb unit, and the size of the target is the same as that of the honeycomb-structure target in test. The results show that the damage area of the honeycomb-structure target is smaller than that of the reinforced concrete target under projectile strikes with approximately the same velocity. The damage range of the honeycomb-structure target is limited within the hexagonal cell getting contact with projectile left other cells with no damage. During the two repeat projectile strikes, the first projectile will deflect to some extent just as single projectile strike. The deflection of the second projectile is larger and is related to the distance between the strike points of the two projectiles. The results show that honeycomb shelter performs good under two repeat projectile strikes.